Genetic evaluation of root and seedling growth of tomato genotypes under cadmium stress - Nadeem, Rujab; Ahmad, Muhammad; Fatima, Maham; Bibi, Naseem; Bisma; Rafique, Muhammad Saad; Tariq, Ayesha; Aqib, Muhammad (Journal of Pure and Applied Agriculture, 2025)
Solanum lycopersicum L. is the most important crop in Pakistan, and concerns are being raised regarding the impact of cadmium (Cd) on tomato plants. This study aimed to determine the genetic differences between twenty tomato genotypes under Cd stress by comparing their root and seedling growth to determine which genotype was the most tolerant to Cd stress. This field experiment was carried out during 2020-2021 in the screen house of the Department of Plant Breeding and Genetics, University of Agriculture Faisalabad, using a completely randomized design (CRD) with two replications. Genotypes were exposed to two treatments: treatment of plants with the specific element under consideration and a stress condition for that element; PT = control (0 ppm) and Cd stress (6 ppm). Various morphological traits were measured, including plant height, root/shoot length, and biomass. Statistical analysis was done by measuring internal consistency through principal component analysis and variance analysis. The results revealed significant differences among genotypes and identified Cd-tolerant tomato varieties suitable for breeding programs. The performance of genotypes was assessed based on key growth parameters, including root length, shoot length, biomass (both fresh and dry), and plant height. Notably, genotypes 17868, 17874, and Money Maker performed well under control conditions, exhibiting superior biomass production and root length. In contrast, Naqeeb and Cchaus showed poor performance, particularly in terms of biomass accumulation and shoot growth, indicating their reduced ability to thrive under optimal conditions. Under Cd stress, genotypes 19860, 17868, and 19865 exhibited favorable performance, primarily in terms of biomass accumulation and root growth, as it maintained relatively higher fresh root weight and shoot biomass compared to other genotypes (Naqeeb and 19899) under the same stress conditions. This study contributes valuable insights into identifying Cd-tolerant tomato genotypes, offering potential improvements for tomato cultivation in Cd-affected regions of Pakistan.